Isolation and screening of multifunctional phosphate solubilizing bacteria and its growth-promoting effect on Chinese fir seedlings - Jiaqi Chen; Guangyu Zhao; Yihui Wei; Yuhong Dong; Lingyu Hou; Ruzhen Jiao (Scientific Reports, 2021)
Abstract Phosphorus-solubilizing microorganisms is a microbial fertilizer with broad application potential. In this study, 7 endophytic phosphate solubilizing bacteria were screened out from Chinese fir, and were characterized for plant growth-promoting traits. Based on morphological and 16S rRNA sequence analysis, the endophytes were distributed into 5 genera of which belong to Pseudomonas, Burkholderia, Paraburkholderia, Novosphingobium, and Ochrobactrum. HRP2, SSP2 and JRP22 were selected based on their plant growth-promoting traits for evaluation of Chinese fir growth enhancement. The growth parameters of Chinese fir seedlings after inoculation were significantly greater than those of the uninoculated control group. The results showed that PSBs HRP2, SSP2 and JRP22 increased plant height (up to 1.26 times), stem diameter (up to 40.69%) and the biomass of roots, stems and leaves (up to 21.28%, 29.09% and 20.78%) compared to the control. Total N (TN), total P (TP), total K (TK), Mg and Fe contents in leaf were positively affected by PSBs while showed a significant relationship with strain and dilution ratio. The content of TN, TP, TK, available phosphorus (AP) and available potassium (AK) in the soil increased by 0.23–1.12 mg g−1, 0.14–0.26 mg g−1, 0.33–1.92 mg g−1, 5.31–20.56 mg kg−1, 15.37–54.68 mg kg−1, respectively. Treatment with both HRP2, SSP2 and JRP22 increased leaf and root biomass as well as their N, P, K uptake by affecting soil urease and acid phosphatase activities, and the content of available nutrients in soil. In conclusion, PSB could be used as biological agents instead of chemical fertilizers for agroforestry production to reduce environmental pollution and increase the yield of Chinese fir.